A filosofia na BNCC-EM: possibilidades, tensões e limites - Estrela, Tatyane (2024)
This work analyzes the possibilities, limits, and tensions of the presence of philosophy in the BNCC-EM based on competencies and skills. After studying the BNCC-EM, in dialogue with recent literature on philosophy teaching and curriculum, a Pedagogical Guide for Teaching Philosophy was produced. This guide aims to assist philosophy teachers in constructing meaningful, interdisciplinary learning situations that mobilize specific knowledge of philosophy, whether articulated in the area of ​​Applied Human and Social Sciences (CHS) or in other curricular spaces such as the Life Project (PV).